2021
DOI: 10.1177/20417314211022242
|View full text |Cite
|
Sign up to set email alerts
|

Artificial decellularized extracellular matrix improves the regenerative capacity of adipose tissue derived stem cells on 3D printed polycaprolactone scaffolds

Abstract: Ideal tissue engineering frameworks should be both an optimal biological microenvironment and a shape and stability providing framework. In this study we tried to combine the advantages of cell-derived artificial extracellular matrix (ECM) with those of 3D printed polycaprolactone (PCL) scaffolds. In Part A, both chondrogenic and osteogenic ECMs were produced by human adipose derived stem cells (hASCs) on 3D-printed PCL scaffolds and then decellularized to create cell free functionalized PCL scaffolds, named a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
21
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
9

Relationship

1
8

Authors

Journals

citations
Cited by 23 publications
(21 citation statements)
references
References 39 publications
(65 reference statements)
0
21
0
Order By: Relevance
“…Several approaches have been adopted to enhance the osteogenic potential of ADSCs. For example, decellularized trabecular bone (Shridhar et al, 2019) and decellularized ECM from osteogenic‐induced ADSCs (Blum et al, 2021) have been reported to enhance the osteogenic differentiation of ADSCs. Synthetic materials such as β‐tricalcium phosphate/collagen‐I fibre scaffolds (Wang et al, 2021), hydrogel scaffolds (Kim et al, 2020), and PCL‐based nanofibrous composite scaffolds (Mansour et al, 2022) have also been employed to stimulate osteogenic differentiation of ADSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Several approaches have been adopted to enhance the osteogenic potential of ADSCs. For example, decellularized trabecular bone (Shridhar et al, 2019) and decellularized ECM from osteogenic‐induced ADSCs (Blum et al, 2021) have been reported to enhance the osteogenic differentiation of ADSCs. Synthetic materials such as β‐tricalcium phosphate/collagen‐I fibre scaffolds (Wang et al, 2021), hydrogel scaffolds (Kim et al, 2020), and PCL‐based nanofibrous composite scaffolds (Mansour et al, 2022) have also been employed to stimulate osteogenic differentiation of ADSCs.…”
Section: Discussionmentioning
confidence: 99%
“…Despite the considerable developments in imaging techniques allowing for comprehensive in vivo and postmortem scaffold evaluation, and even the creation of 3D virtual models [ 29 , 30 ], little attention has been paid to the refinement and updating of histopathological techniques, which remain the basic tool for assessments of scaffold morphology, biocompatibility, and interactions with the surrounding cells. The standard techniques used today only allow for evaluations of selected representative fragments, where the scaffold is often cleared, melted, or swollen, and it is not possible to obtain the full cross-section view with the preserved scaffold’s honeycomb-like structure [ 31 , 32 ].…”
Section: Discussionmentioning
confidence: 99%
“…Subsequently, the self-made PCL-scaffold was compared to a commercially available PCL-scaffold, which was successfully used for chondrogenic and osteogenic tissue engineering in an earlier study [28]. In vitro cultivation with human ASCs revealed comparable cell viability, distribution, and proliferation capacity on both priorly sterilized PCL-scaffolds.…”
Section: Discussionmentioning
confidence: 99%